A winter in new york eaudiobook A novel. - Silver, Josie (Books on Tape, 2023)
A young chef stumbles on a secret family recipe that might lead her to the love—and life—she’s been looking for in this stunning novel from the New York Times bestselling author of One Day in December . A POPSUGAR BEST BOOK OF THE YEAR When Iris decides to move to New York to restart her life, she realizes she underestimated how big the Big Apple really is—all the nostalgic movies set in New York she’d watched with her mom while eating their special secret-recipe gelato didn’t quite do it justice.  But Bobby, Iris’s best friend, isn’t about to let her hide away. He drags her to a famous autumn street fair in Little Italy, and as they walk through the food stalls, a little family-run gelateria catches her eye—could it be the same shop that’s in an old photo of her mother’s? Curious, Iris returns the next day and meets the handsome Gio, who tells her that the shop is in danger of closing. His uncle, sole keeper of their family’s gelato recipe, is in a coma, so they can’t make more. When Iris samples the last remaining batch, she realizes that their gelato and her gelato are one and the same. But how can she tell them she knows their secret recipe when she’s not sure why Gio’s uncle gave it to her mother in the first place? Iris offers her services as a chef to help them re-create the flavor and finds herself falling for Gio and his family. But when Gio’s uncle finally wakes up, all of the secrets Iris has been keeping threaten to ruin the new life—and new love—she’s been building all winter long.